Campus‐based student experiences of learning technologies in a first‐year science course. (17th September 2012) - Ellis, Robert; Weyers, Mark; Hughes, Jane
Abstract: This study reports on an investigation into the campus‐based experience of university students studying mammalian physiology that was significantly supported with learning technologies. The design of the course enabled the students to interrogate the key ideas that they came across in their lectures and laboratories through online activities which prepared the students for practical classes. Close‐ended questionnaires were used to uncover qualitative variation in the population sample, particularly the differences in the concepts of learning technologies and approaches to learning technologies. Qualitative variation in concepts of, and approaches to, learning technologies was found to be significantly associated with variation in academic achievement. The outcomes have important implications for the approaches to teaching of campus‐based experiences of learning supported by learning technologies when we seek to support all students to realise their learning outcomes in technology‐mediated processes